LEV VLADIMIROV’S GENERAL BOOK HISTORY CONCEPTION - AKSTINAITĖ, EGLĖ (Knygotyra, 2015)
The aim of the article is to reveal Lithuanian book scientist’s L.Vladimirov’s, who was one of few people from Eastern Europe and the only from neighbour states who researched world book history, general book history conception (in Lithuanian: Knygos istorija: senovė, viduramžiai, renesansas, XVI–XVII amžius, Vilnius, 1979; in Russian: Всеобщая история книги: древний мир, средневековье, возрождение, XVII век. Москва, 1988). The article analyses L.Vladimirov’s world outlook which partially influenced the methodological solutions of his researches. Also Marxism-Leninism ideology impact on his works is assessed, the main Eastern and Western Europe works of the field are discussed (works by S. Dahl, S. H. SteinAbstractberg, D. C McMurtrie et al.). The main conclusion is that L.Vladimirov’s Book History is history synthesis, which aimed at presenting as broad as possible review of the problematics. It is true to say that L.Vladimirov’s general book history concept is not whole and finished methodologically and the author himself did not define it. But as the first work of the character in Lithuania, this book is important because of its incorporation of Lithuanian book history into the world context. Hence, as this L.Vladimirov’s work is important to Lithuania, we might say that it is urgent inside the boarders of the former USSR because of broad geographical context; and to Europe it is interesting as synthesis of eastern and western knowledge.